Evolutionary modification of gastrulation in Parvulastra exigua, an asterinid seastar with holobenthic lecithotrophic development. Issue 2 (19th January 2021) - Byrne, Maria; Selvakumaraswamy, Paulina
Abstract: Gastrulation is a fundamental morphogenetic process in development. In echinoderms with ancestral‐type development through feeding larvae, gastrulation involves radially symmetrical invagination of cells around the blastopore. Gastrulation in the seastar Parvulastra exigua, a species with non‐feeding larvae deviates from this pattern. Microinjection of cells with fluorescent lineage tracer dye revealed that early blastomeres contribute unequally to ectoderm and endoderm. In embryos injected at the two‐cell stage, asymmetry was evident in the fluorescence at the top of the archenteron and animal pole ectoderm. Archenteron elongation is driven by asymmetrical involution of cells with more cells crossing the blastopore on one side. Lineages of cells injected at the four‐cell stage also differed in allocation to endoderm and ectoderm. In embryos injected at the eight‐cell stage ectodermal and endodermal fates were evident reflecting the animal and vegetal fates determined by third cleavage as typical of echinoderms. Modification of gastrulation associated with evolution of development in P. exigua shows that this foundational morphogenetic process can be altered despite its importance for subsequent development. However, observations of slight asymmetry in the lineage fates of blastomeres in asterinids with planktotrophic development indicates that gastrulation by asymmetrical involution in P. exigua may be a hypertrophic elaboration of a pre‐existing state in ancestral‐type development. As for echinoids with lecithotrophic development, involution as a mechanism to contribute to archenteron elongation may be associated with the impact of extensive maternal nutritive reserves on the mechanics of cell movement and a novel innovation to facilitate early development of the adult rudiment. Abstract : Modified gastrulation in a seastar Gastrulation is a fundamental morphogenetic process in development that in echinoderms, usually involves radially symmetrical invagination of cells around the blastopore. In the seastar Parvulastra exigua, a species that has evolved lecithotrophic larvae and holobenthic development, microinjection of cells with fluorescent lineage tracer dye revealed that early blastomeres do not contribute equally to ectoderm and endoderm. In contrast to the ancestral‐type state, archenteron elongation is driven by asymmetrical involution of cells with more cells crossing the blastopore on one side as indicated by the arrows. This evolutionary change may be associated with the switch to lecithotrophy. Highlights: Gastrulation in the seastar Parvulastra exigua is asymmetrical. Archenteron elongation involves asymmetrical involution. Asymmetrical involution may be an elaboration of traits in ancestral‐type development.